Long Noncoding RNA MANTIS Facilitates Endothelial Angiogenic Function. Issue 1 (4th July 2017) - Leisegang, Matthias S.; Fork, Christian; Josipovic, Ivana; Richter, Florian Martin; Preussner, Jens; Hu, Jiong; Miller, Matthew J.; Epah, Jeremy; Hofmann, Patrick; Günther, Stefan; Moll, Franziska; Valasarajan, Chanil; et al.
Abstract : Background: The angiogenic function of endothelial cells is regulated by numerous mechanisms, but the impact of long noncoding RNAs (lncRNAs) has hardly been studied. We set out to identify novel and functionally important endothelial lncRNAs. Methods: Epigenetically controlled lncRNAs in human umbilical vein endothelial cells were searched by exon-array analysis after knockdown of the histone demethylase JARID1B. Molecular mechanisms were investigated by RNA pulldown and immunoprecipitation, mass spectrometry, microarray, several knockdown approaches, CRISPR-Cas9, assay for transposase-accessible chromatin sequencing, and chromatin immunoprecipitation in human umbilical vein endothelial cells. Patient samples from lung and tumors were studied for MANTIS expression. Results: A search for epigenetically controlled endothelial lncRNAs yielded lncRNA n342419, here termed MANTIS, as the most strongly regulated lncRNA. Controlled by the histone demethylase JARID1B, MANTIS was downregulated in patients with idiopathic pulmonary arterial hypertension and in rats treated with monocrotaline, whereas it was upregulated in carotid arteries of Macaca fascicularis subjected to atherosclerosis regression diet, and in endothelial cells isolated from human glioblastoma patients. CRISPR/Cas9-mediated deletion or silencing of MANTIS with small interfering RNAs or GapmeRs inhibited angiogenic sprouting and alignment of endothelial cells in response to shear stress. Mechanistically, the nuclear-localized MANTIS lncRNA interacted with BRG1, the catalytic subunit of the switch/sucrose nonfermentable chromatin-remodeling complex. This interaction was required for nucleosome remodeling by keeping the ATPase function of BRG1 active. Thereby, the transcription of key endothelial genes such as SOX18, SMAD6, and COUP-TFII was regulated by ensuring efficient RNA polymerase II machinery binding. Conclusion: MANTIS is a differentially regulated novel lncRNA facilitating endothelial angiogenic function. Abstract : Supplemental Digital Content is available in the text.